New Nanocomposite Made of Cashew Apple Bagasse Lignin and Fe3o4 for Immobilizing of Lipase B from Candida Antarctica Aiming at Esterification - Casagrande-Denardin, J; Melo-Freire, R (John Wiley and Sons Ltd, 2021)
BACKGROUND: Novel magnetite-lignin hybrid materials were synthesized using lignin from cashew apple bagasse (CAB) and iron oxide nanoparticles (magnetite, Fe3O4). The new material, termed MNs/Lig (magnetite conjugated with lignin), was used as a support for the immobilization of lipase B from Candida antarctica (CAL─B), aiming to obtain an active and stable biocatalyst that is easily recoverable from the reactional medium. RESULTS: The magnetite/lignin composite showed a higher thermal stability than pure lignin, and it presented good magnetic properties, both before and after the immobilization procedure. The immobilization yield was higher using the unaltered MN/Lig as a support than when using the glutaraldehyde-activated MNs/Lig (MNs/Lig_GA), with yields of 66.6% and 40.0%, respectively. The presence of Triton X-100 did not influence the immobilization yield or the thermal stability of the biocatalyst when employing the unaltered MNs/Lig. However, it influenced the thermal stability of the lipase immobilized on MNs/Lig_GA, lowering the biocatalyst stability, which showed a half-life 11-fold lower than that of MNs/Lig_GA_CALB. The biocatalysts were tested with regards to the synthesis of ethyl oleate using oleic acid and ethanol as substrates, and 2-ethylhexyl oleate (a biolubricant) using oleic acid and 2-ethyl-hexanol as substrate. The conversions obtained by MNs/Lig_Tri_CALB were 88.2% and 76.7% for ethyl oleate and 2-ethylhexyl oleate, respectively. CONCLUSION: The novel strategy presented in this work for obtaining a biocatalyst using synthesized hybrids (MNs/Lig) may be a promising route for lipase immobilization because it can be considered environmentally benign and it shows a strong potential use in several reactions of industrial interest. © 2021 Society of Chemical Industry (SCI). © 2021 Society of Chemical Industry (SCI).